2020
DOI: 10.2147/ijn.s250911
|View full text |Cite
|
Sign up to set email alerts
|

<p>Honokiol-mesoporous Silica Nanoparticles Inhibit Vascular Restenosis via the Suppression of TGF-β Signaling Pathway</p>

Abstract: Introduction The main pathological mechanism of restenosis after percutaneous coronary intervention (PCI) is intimal hyperplasia, which is mainly caused by proliferation and migration of vascular smooth muscle cells (VSMCs). Our previous study found that honokiol (HNK), a small-molecule polyphenol, can inhibit neointimal hyperplasia after balloon injury, but its specific mechanism is still unclear. Moreover, poor water solubility as well as low bioavailability of honokiol has limited its practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 438 Numerous studies have shown that nanoparticles can be exploited to target and regulate vascular endothelial and VSMCs functions, including cell proliferation, migration, inflammation, senescence, and apoptosis. 36 , 339 , 439 441 There are particularly strong data indicating that proliferation and migration of endothelial dysfunction and VSMCs are vital to vascular aging-related diseases, such as atherosclerosis, hypertension, vascular stenosis and restenosis, and MI. 175 , 176 Therefore, nanoparticle-mediated anti-proliferation and anti-apoptotic therapies hold great promise in preventing vascular aging-related disorders.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
See 1 more Smart Citation
“… 438 Numerous studies have shown that nanoparticles can be exploited to target and regulate vascular endothelial and VSMCs functions, including cell proliferation, migration, inflammation, senescence, and apoptosis. 36 , 339 , 439 441 There are particularly strong data indicating that proliferation and migration of endothelial dysfunction and VSMCs are vital to vascular aging-related diseases, such as atherosclerosis, hypertension, vascular stenosis and restenosis, and MI. 175 , 176 Therefore, nanoparticle-mediated anti-proliferation and anti-apoptotic therapies hold great promise in preventing vascular aging-related disorders.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“… 456 Wei et al packaged honokiol in MSNs and assembled them into honokiol-MSNs, and found that they effectively inhibited VSMCs proliferation and migration through alleviating Smad3 phosphorylation. 441 In another study, researchers employed layered double hydroxide (LDH) nanoparticles to deliver LMWH for the prevention of vascular restenosis, and found that LMWH-LDH nanoparticles were rapidly internalized by VSMCs and dramatically attenuated VSMCs proliferation and migration. 457 Notably, the application of 17β-estradiol (17-βE), ω-3-polyunsaturated fatty acids (PUFAs), and C6-ceramide (CER) in the treatment of vascular restenosis is limited by their extensive protein binding and lipophilicity.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…The honokiol-loaded MSNPs demonstrated inhibitory effects on the proliferation and migration of vascular smooth muscle cells (VSMCs) and effectively suppressed intimal thickening in a rat model of balloon injury. This nanosystem presents a promising strategy for preventing restenosis and enhancing the therapeutic potential of honokiol in the context of vascular interventions [ 39 ].…”
Section: Restenosismentioning
confidence: 99%
“…Additionally, drug-loaded nanoparticles show promise in the treatment of severe and life-threatening atherosclerotic lesions in coronary heart disease (CHD) [ 38 ]. Mesoporous silica nanoparticles (MSNPs) enhance the therapeutic effects of honokiol in inhibiting neointimal hyperplasia [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, quercetin (Khandelwal et al, 2012) and salvianolic acid A (SAA) (Sun et al, 2012) were also found to inhibit proliferation of VSMCs too. Intriguingly, a green tea polyphenol, epigallocatechin-3-gallate (EGCg), suppressed neointimal hyperplasia (NIH) in rabbit model by inhibiting the proliferation of VSMCs via inactivation of MAPKs pathway In a recent study, Wei delivered mesoporous silica nanoparticles encapsulated honokiol (HNK), a small molecule polyphenol after balloon injury and HNK greatly suppressed intimal thickening by reducing phosphorylation of Smad3 (Wei et al, 2020).…”
Section: Plant-based Approach For Ihmentioning
confidence: 99%